Uyghur nation reform and revolution on the Russia-China frontier - Brophy, David John (Harvard University Press, 2016)
Along the Russian-Qing frontier in the nineteenth century, a new political space emerged, shaped by competing imperial and spiritual loyalties, cross-border economic and social ties, and revolution. David Brophy explores how a community of Central Asian Muslims responded to these historic changes by reinventing themselves as the Uyghur nation.